(untitled) - Løkkeborg, Svein (Rome, 2005)
Over the last two decades, concerns about the impact of towed fishing gears such as trawls and dredges on benthic habitats and organisms have increased. This publication reviews the most recent experimental studies of the impact of towed fishing gears on benthic communities. Otter trawls, beam trawls and scallop dredges are likely to have different physical impacts on the sea bed owing to their different catching techniques. The most noticeable physical effect of otter trawling is the furrow created by the doors. Beam trawling and scallop dredging cause a flattening of irregular bottom topography by eliminating natural features. The long-term effects of fishing activities have not been investigated although several studies provide clear evidence of short-term consequences.
Keywords: Trawls and trawling,Lưới và đánh bắt cá; Environmental aspects,Khía cạnh môi trường